UPAYA MENINGKATKAN KEMAMPUAN BACAAN SURAH AL-IKHLAS MELALUI MEDIA PUZZLE PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS 1 MI AL-MAGFIRAH BINA JAYA - Pahmi Kasim; Mujahid Damopolii; Ruwiah A. Buhungo (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine the use of Puzzle Media in Improving the Reading Ability of Q.S Al-Ikhlas in the Al-Qur'an Hadith Subject of Grade 1 at MI Al-Maghfirah. This research is a Classroom Action Research (CAR). The subjects of this study were Grade 1 teachers and all grade 1 students of MI Al-Magfirah Bina Jaya, Tolangohula District, Gorontalo Regency. The object of this study was to determine the Use of Puzzle Media in Improving the Reading Ability of Q.S Al-Ikhlas in the Al-Qur'an Hadith Subject of Grade 1 MI Al-Magfirah Bina Jaya, Tolangohula District, Gorontalo Regency. The results of this study indicate that in grade 1 students of MI Al-Magfirah Bina Jaya with the application of Puzzle Media in Learning Al-Qur'an Hadith material Q.S Al-Ikhlas. The use of Puzzle Media can Improve students' ability to read Q.S Al-Ikhlas better